Epidemiological Assessment of the First Results of the National Program of Immunization of Young Children against Pneumococcal Infection in Russia - N. I. Brico; N. N. Tsapkova; V. A. Sukhova; A. N. Gerasimov; R. V. Polybin; I. E. Turina; P. I. Dryagileva; N. V. Kholodnova; Yu. Yu. Khetagurov; I. V. Feldblum; A. V. Polushkina; L. N. Titova; et al. (Эпидемиология и вакцинопрофилактика)
Pneumococcal infections are among the most common infections are an important cause of morbidity and mortality worldwide, including Russia. At the end of 2014 in the national immunization schedule countries introduced vaccination against pneumococcal infection The aim of study. To assess the epidemiological effectiveness of vaccination against pneumococcal infection in young children selectively in different territories of the Russian Federation 2 years later from its beginning Materials and methods. In the course of epidemiological observational analytical research of type «case-control» data were obtained on the incidence in vaccinated and unvaccinated against pneumococcal infection in children from 2 months to 2 years We analyzed 1422 outpatients and 356 case histories of children in several cities (Moscow, Smolensk, Sevastopol, Perm, Tyumen, Barnaul). The results are subjected to statistical processing The results and discussion Established that there is a reliable causal connection between the lack of vaccination of children against pneumococcal infection and incidence of diseases. Shows high prophylactic efficacy of vaccination of children up to 2 years. Received in outpatient and inpatient facilities, evidence suggests that the incidence of invasive and non-invasive forms of pneumococcal infection was significantly lower in the vaccinated children It was revealed that the vaccination coverage against pneumococcal infection in children from 2 months to one year and the second year of life was 51 and 40% respectively. Vaccination in the first six months of life in 2016 received only 25% of children. A high proportion of the parent's refusal of vaccination of children (54.2%), and high frequency medical taps (9.7%) from vaccination.